Spillover Effects and Political Yardstick Competition in Local Public Spending in Indonesia - Akbar, Muhammad Reyhan; Muljarijadi, Bagdja (UI Scholars Hub, 2024)
This study aims to test the presence of spillover effects and political yardstick competition in both mandatory and discretionary spending among local governments in Indonesia. A spatial econometrics model was employed to evaluate data from 410 districts/municipalities in Indonesia from 2010 to 2018. The findings confirm spillover effects in spending decisions among local governments. The empirical analysis also reveals that political factors drive horizontal interactions in mandatory spending, while such influences are absent in discretionary spending.